Billing tools in the real estate management system as a factor of increasing economic efficiency - Ivanchenko, Anatoliy; Korytko, Dmytriy (Ways to Improve Construction Efficiency, 2025)
The article presents an in-depth analysis of modern billing tools in the real estate management system and the provision of utility services, which are considered an important element of the digital infrastructure of enterprises in the industry. It is determined that billing systems have long gone beyond the classical functionality of charging and accounting for payments, turning into extensive information-analytical platforms capable of accumulating, structuring and processing significant amounts of data on consumers, resource consumption indicators, tariffs, technical condition of facilities and financial obligations. It is shown that the use of such systems ensures high accuracy of accruals, minimizes the risks of errors, increases the transparency of relationships between service providers and users, contributes to the reduction of receivables and strengthens the financial stability of enterprises. Particular attention is paid to the integration capabilities of billing platforms. It is proven that their combination with online payment services, CRM systems, mobile applications and electronic offices forms a single digital management space, optimizes communications with consumers, accelerates data processing and improves the quality of service. Such integration provides operational access to analytical information, allows you to model financial scenarios, plan income and expenses, and also increases the efficiency of management decisions in real time. Promising directions for the development of billing tools in the context of the digitalization of the real estate market are outlined: the use of artificial intelligence and machine learning for predictive analysis, the use of IoT devices for automated data collection, the development of dynamic tariff formation modules, the personalization of services and the implementation of flexible models of interaction with consumers. It is emphasized that the improvement of billing systems is a key factor in increasing the economic efficiency of utilities, contributes to cost optimization, improves the quality of services and ensures the formation of an innovative model of real estate management.